Evaluation of the gelling ability of actomyosin-paramyosin from giant squid mantle (Dosidicus gigas) - Santacruz-Ortega, H. (2021)
The process of thermal gelation involves protein denaturation, leading to the exposure of functional groups to form new interactions; these conformational changes favour protein-water-protein interactions and help to stabilise the gel. It is known that in muscle proteins, myofibrillar proteins such as myosin are responsible for the main functional properties; however, in invertebrate species, actin and paramyosin exert an influence on the rheological properties of the gels. Therefore, in the present work, the gelling property of the actomyosin-paramyosin complex was studied. There were significant differences (p < 0.05) in hardness and water-retention capacity, which was higher for actomyosin-paramyosin isolate (API) than for mantle proteins (MP). This may have been due to its structure being more porous than that of MP, which is agglomerated. The API system favoured protein-protein and water-protein interactions; these formed stronger cross-links, which in turn favoured gelling. Moreover, the presence of sarcoplasmic proteins may be more of a physical-chemical impediment rather than hydrolysis caused by endogenous proteases.